AUGMENTED REALITY UNTUK PENGENALAN SATWA PADA KEBUN BINATANG GEMBIRA LOKA YOGYAKARTA - Franz, Annafi’; Lestari, Uning; Andayati, Dina (Jurnal Script, 2014)
ABSTRACTCurrently the android operating system is the most popular operating system for mobile handheld devices. Applications that can be installed on the android operating system which will be more and more users. The current technology is emerging augmented reality technology. Augmented reality technology is a merger between the virtual object and the real object. Merging virtual object and the real object is what will generate more information and complet. The information contained on Yogyakarta Gembira Loka zoo today just a little bit of text information about each animal. If using augmented reality, then the information on the animals at the Yogyakarta Gembira Loka zoo will be faster and much that is presented to the user application. In the process of making augmented reality application systems require data and images of animals. The tool used the eclipse as android editor, Notepad++ as PHP editor, and MySQL for the database designer. The method used in this data collection method that uses interviews and library research methods. This study aims to make it easier for users to find information faster, and a lot of detail about the animals living in the Yogyakarta Gembira Loka zoo With a system of this application, then the information on the data and the animals can be added easily and quickly updated.Key words: android, augmented reality, zoo.